TOWARDS A TRANSFORMATIVE CIVIC EDUCATION MODEL: RECONSTRUCTING DEMOCRATIC CITIZENSHIP THROUGH UNIVERSITY–PESANTREN SYNERGY - Abd. Rozak; Zaenul Slam; Otong Suhyanto; Yusran Ilyas; Ahmad Ta’rifin (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
The increasing complexity of democracy in the Indonesian context requires the reconstruction of civic education that goes beyond the transmission of formal curriculum to a transformative formation process, especially in the ecological system of Islamic boarding schools. This study aims to reconstruct civic education in Indonesian student Islamic boarding schools through the development of a Transformative Citizenship Formation Model that explains how democratic citizenship is formed through the interaction between higher education and the pesantren environment. Using Constructivist Grounded Theory, this research was conducted at the Rahmaniyah Islamic Boarding School in Semarang, Indonesia. Data were collected through in-depth interviews with eight participants and participant observations, then analyzed through iterative coding, constant comparison, and theoretical integration based on Charmaz's constructivist approach. The findings of the study reveal that civic education is not formed through academic or religious spaces separately, but is reconstructed through a continuous negotiation process between the academic experience at UIN Walisongo Semarang and the formation of character in pesantren life. This process forms three main transformations: the integration of civic education through the synergy of universities-Islamic boarding schools, the negotiation of democratic citizenship in the two educational ecologies, and the transformation of Islamic-democratic values into Muslimah civic agency which is reflected in leadership, social participation, and community service. These findings contribute to building the idea that pesantren is not only a space for the reproduction of religious values, but also a space for the production of democratic citizenship through the encounter between faith, knowledge, and social responsibility. This study offers a Transformative Citizenship Formation Model to explain the process.